2017
DOI: 10.1002/lt.24752
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of transarterial chemoembolization–induced complete pathological response in patients undergoing liver resection and transplantation for hepatocellular carcinoma

Abstract: Transarterial chemoembolization (TACE)-induced complete pathological response (CPR) is known to improve postresection outcomes of hepatocellular carcinoma (HCC). We aimed to assess the prognostic effects of CPR after preoperative TACE for HCC in patients who underwent hepatic resection (HR) or liver transplantation (LT). The clinical outcomes of patients showing CPR after HR (n = 110) or LT (n = 233) were analyzed. The control groups comprised patients with minimal recurrence risk as naïve single HCC ≤ 2 cm fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…The transhepatic approach, dividing the hepatic parenchyma to expose the paracaval portion, is a feasible method used to reduce the risk of tumor handling-associated tumor spread. Downstaging with preoperative TACE had been attempted, but its therapeutic effect was worse than expected 711. HR, used only a few months after TACE, should be avoided because the integrity of the HCC cells is loosened, by which the risk of intraoperative tumor spread increases.…”
Section: Discussionmentioning
confidence: 99%
“…The transhepatic approach, dividing the hepatic parenchyma to expose the paracaval portion, is a feasible method used to reduce the risk of tumor handling-associated tumor spread. Downstaging with preoperative TACE had been attempted, but its therapeutic effect was worse than expected 711. HR, used only a few months after TACE, should be avoided because the integrity of the HCC cells is loosened, by which the risk of intraoperative tumor spread increases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the extent of tumor necrosis correlated with prognosis. 12,14 However, it remains challenging for TACE per se to eliminate tumor cells entirely and the residual viable tumor cells are the important sources of rapid recurrence and tumor progression that remarkably deteriorate the patient prognosis. In a large-scale study analyzing over 3000 cases, the pathologically proved complete necrosis can only be achieved in 22.4% of the patients who received TACE treatment alone; and even for patients subjected to combined therapy of TACE and thermal ablation, pathological CR rate merely increased to 26.0%.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…15 Furthermore, it is much more difficult to achieve pathological complete necrosis compared to imaging criteria, and previous studies reported that residual tumor cells can be found in most (89%) of the lesions which were determined as CR in imaging analysis. [12][13][14] Therefore, it is critical to explore novel strategies for enhancing liver tumor eradication.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
See 2 more Smart Citations